Fauna de Coleoptera Melolontidae en el Rancho La Joya, Atlixco, Puebla, México - Aragón, Agustín; Morón, Miguel Angel; Tapia Rojas, Ana María; Rojas García, Raúl (Instituto de Ecología, A.C., 2001)
Preliminary analysis of the chafer beetle fauna of La Joya farm, near Atlixco, Puebla, Mexico is presented. Data were obtained during 1996-1999 with 130 hours of collecting effort in crop lands located at 1,700 m altitude. Records of 3 subfamilies, 6 tribes and 21 species of the genera Phyllophaga, Macrodactylus, Anomala, Cyclocephala, Strategus and Ligyrus represented by 1,563 adults and 292 larvae are included. Specific diversity is concentrated in the genera Phyllophaga (8 spp.) and Anomala (7 spp.). Phyllophaga ravida (Blanch.) was the most abundant species in the samples of adults. Larvae of Ph. ravida and Ph. ilhuicaminai Morón produces severe damage to the roots of Limonium sinuatum (L.) crops. Low diversity and high predominance of Melolonthidae species in this locality is the result of historical use of agricultural practices widely applied to the crop lands in the Plateau and valleys of Central Mexico.